(untitled) (Global Journal of Management and Business Research, 2018)
Customers of multinational enterprises (MNEs) exist almost everywhere. Cross-border B2C e-commerce is expected to double by 2022 according to Forrester Research. How do MNE#x2019;s efficiently leverage their brand in a uniform front across products and geographic markets? How do they assure that the culture behind the brand looks the same to a customer regardless of where they engage the company? The author shows how a one-ness strategy was applied in an MNE case study. The author extracts twenty propositions from the findings in this case and ultimately guides a discussion on an efficacious unified culture. Absent this understanding, the risk of revenue loss is enhanced significantly.